ROLE OF AYURVEDA IN PEDIATRIC ASTHMA: A HOLISTIC TREATMENT PERSPECTIVE - Dr.Akshay Gurav; Prof. Dr. Hemant Toshikhane; Dr. Swapnil Raskar; Dr. Asha Hosur (The Bioscan, 2025)
Bronchial asthma is a long-standing inflammatory disorder resulting from inflammation of the airway mucosa and spasms of the bronchial smooth muscles. It presents with frequent spells of wheezing, breathlessness, coughing, and quickened breathing. Bronchial asthma is one of the most chronic conditions that affect people of all ages and socioeconomic backgrounds. Unlike adults, in children, severity is associated with the duration of wheezing, lung functioning, and the risk of allergens, as children are more sensitive to allergens. As per Ayurveda, Shwasa Roga is mainly caused by the Vata and Kapha doshas. The clinical features of bronchial asthma closely resemble those described for Tamaka Shwasa. Among children, Tamaka Shwasa is one of the most commonly encountered types of Shwasa.Such a case of Tamaka Shwasa, i.e., childhood Asthama had approached our clinic and was managed by the Ayurvedic line of treatment with classical Virechana followed by Shamanaushadi, for which the patient got a satisfactory result. KEYWORDS Bronchial Asthma, Tamaka Shwasa, Virechana, Ayurveda, Childhood Asthama